Factors Affecting Work Effectiveness of Nurses at Bontang Taman Husada Hospital - Hajar, ST; Melda, Byba; Wardani, Ratna (Babali Nursing Research, 2023)
Introduction: Medical services are inseparable from the services provided by health workers, especially nurses. The achievement of optimal work effectiveness is an assessment of the effectiveness of nurses' work as an effort to assess nurses' achievements at work. Assessment of work effectiveness in performance indicators is a reliable tool as a control of human resources and productivity, but in fact nurse performance is a problem in all nursing services. The purpose of the study was to analyze the factors that affect the effectiveness of nurses' work at Taman Husada Bontang Hospital. Methods: The research design was in the form of observational research using a cross sectional design. The population of all nurses at Taman Husada Bontang Hospital was 212 respondents. The sample in this study was nurses at Taman Husada Bontang Hospital totaling 136 respondents with simple random sampling. Independent variables factor productivity, satisfaction, and competence. Dependent variable of the effectiveness of the nurse's work. Results: The results showed that there was a relationship between productivity factors (p = 0.021), satisfaction (p = 0.000), competence (p = 0.000) on the effectiveness of nurses' work. Multivariate analysis shows that the most influential variable on the effectiveness of nurses' work at Taman Husada Bontang Hospital is satisfaction with the significance level of p = 0.000 and B = 0.333. Conclusion: Work effectiveness is needed in improving the quality of services in hospitals, so that improving the quality of human resources must be optimized. Work effectiveness is a deliberate ability to do something better to achieve certain goals by emphasizing compliance at work and relating to work results. So that leaders in hospitals must continue to pay attention to the welfare of nurses to improve the effectiveness of their work in providing excellent health services.